Selection of social work as an academic major among male and female undergraduate baccalaureate students - Rogers, LaTra Tracy, author; Morgan, George, advisor; Buchan, Vicky, advisor (Colorado State University. Libraries, 2008)
The purpose of this research was two-fold. First, this research used a questionnaire to identify factors impacting female and male undergraduate students' motivations for selection of and experiences within the social work major. Second, this research seeks to further investigate the experiences of male BSW students in a female dominated major. There were 166 participants, 141 females and 23 males from two undergraduate social work programs in Colorado who completed a 32-item questionnaire that was divided into three parts: motivations, experiences, and demographics. Hanson and McCullagh (1995) identified two factors from 12 items about motivation to select a social work program. Factor 1 was labeled Service to Others and Factor 2 was labeled Job Self Interest. Students in the current study rated the Service to Others items higher than Job Self Interest items, and females rated the Service to Others scale as more important motivators than did males. The findings of the study revealed that there were three motivation differences based on gender, two motivation differences based on age, and one motivation difference based on marital status. There were four experience differences found based on grade level, three experience differences based on Prior Exposure to a Social Worker, and one experience differences based on ethnicity. Having experienced a psychosocial crisis was not rated as an important motivator to select the major, but males, older students, married students, and those with no prior exposure to a social worker were more likely to rate it as an important motivator than were females, younger, and unmarried students. There were few differences in experiences during the major based on demographics. In conclusion, both female and male participants in this study have shed light on key motivation and experience factors impacting female and male undergraduate selection of and experiences within the social work major. The male participants who were involved in the follow-up interviews and offered their personal reflections, have helped to shed insight on male experiences within social work and how the profession can attract more males into social work programs.
Keywords: academic major; baccalaureate; female social work students; major selection; male social work students; motivating factors; social work; undergraduate; undergraduate social work; social work; gender studies; higher education